Epigenetic shaping of sociosexual interactions : from plants to humans - Yamamoto, Daisuke, 1954- (Advances in genetics, 2014)
Epigenetic Shaping of Sociosexual Interactions: From Plants to Humans is the first attempt to interpret the higher social functions of organisms. This volume covers an extraordinarily wide range of biological research and provides a novel framework for understanding human-specific brain functions. Covers an extraordinarily wide range of biological research Provides a novel framework for understanding human-specific brain functions.